The Little Gray Bunny - McGrath, Barbara Barbieri 1954-; Kim, Violet (Watertown, MA : Charlesbridge, 2013)
In this version of "The Little Red Hen," set at a farm, the other animals eat and play while the little gray bunny does all the chores in the barn, until one day he teaches them a lesson about laziness.
Accelerated Reader AR
Keywords: Folklore; Rabbits -- Folklore; Animals -- Juvenile literature. -- Folklore; Laziness -- Folklore